Gender Issue in Transportation Sector of Nigeria: A Case Study of Lokoja, Kogi State - Richard, Shaibu Hasssan; Okon, Emmanuel Okokondem (American International Journal of Social Science Research, 2018)
This paper aimed at finding out what constraint women in transport sector in Lokoja and why employers are reluctant in employing women in the sector? The null hypothesis is that women constraints have no significant effect in transportation sector in Lokoja. Information for the paper was basically from the questionnaire survey method Data generated were analyzed using descriptive statistics such as mean, simple percentages and graphical illustrations. Chi-square analysis was used to test the formulated hypothesis. The result reveals that women constraints have significant effect in transportation sector in Lokoja. Transport business in Lokoja is so dominated by male counterpart and yet some routes are not adequately covered. Based on the aforementioned findings, it is recommended that social attitude in Lokoja, Kogi state and Nigeria in general should be changed in favour of women employment in transport sector. The government of Kogi state should establish driving schools and transport scheme meant to enhance the livelihood of women. The National Union of Road Transport Worker (NURTW) should encourage women to invest in the sector.